A framework and implementation of Customer Platform-connection manufactory to service (CPMS) model in product service system. (1st September 2019) - Zhang, Xianyu; Ming, Xinguo; Liu, Zhiwen; Qu, Yuanju; Yin, Dao
Abstract: With the continuous improvement of living standards, customers are gradually pursuing products which are individualization and entertainment. The traditional large-scale manufacturing mode cannot meet the individual needs of customers. The production mode of the enterprises has been changed from the traditional inventory mode to the customization manufacturing mode driven by the customer orders. Furthermore, the simple customization model cannot meet the industrial needs in the open and networked era. Therefore, there is a lack of an innovative manufacturing mode that not only meets the individual needs of customers, but also adapts to today's open and networked environment. In this paper, a new customization model was proposed, which is a continuously improved customization model called CPMS (Customer Platform-connection Manufactory to Service). By means of research methodology of literature review and analysis, the birth, concept, and evolution of CPMS in PSS are discussed. Through analysing the development of industry, combining with the existing analysis and projects we involved in, and the method of system engineering analysis, an overall framework of CPMS model is derived. At last, a case study for implementation of CPMS in the car industry has been given. Under this model, enterprises can improve the flexible production capacity of production line, reduce the production cost, reduce inventory, improve the modular configuration of products, and etc. Moreover, it can provide some reference value for enterprises to plan, design, implement and apply a new customization production model that conform to the requirements of the new era of open and networked.